Macular pucker and cataract treated with phacoemulsification and IOL implantation combined with small-gauge pars plana vitrectomy: a comparison of outcomes with and without femtosecond laser assistance - Chao, Howard Wen-Haur; Cheng, Cheng-Kuo; Liou, Shiow-Wen; Chao, Hsiao-Ming (Frontiers in Medicine, 2025)
ObjectivesAge-related cataracts and macular pucker are increasingly common. Standard treatment combines phacoemulsification, IOL implantation and small gauge vitrectomy. Recent advancements and acceptance of femtosecond laser (FSL) assistance in cataract surgery have improved precision and outcomes. However, evidence regarding the efficacy and safety of FSL-assisted phacovitrectomy, particularly in Oriental patient populations with distinct anatomical and genetic characteristics, remain limited. This study aims to address this critical gap by comparing the safety and post-operative outcomes of 23- or 25-gauge phacovitrectomy for stage 3 macular pucker and medium density cataract with versus without FSL-assistance (FSLA), in an Oriental patient cohort.MethodsPatients with stage 3 macular pucker and medium-density cataract were recruited and divided into two age-matched groups: group 1 (n = 13) underwent conventional phacovitrectomy without FSLA, and Group 2 (n = 13) underwent phacovitrectomy with FSLA. Evaluations included pre- and postoperative best-corrected visual acuity (BCVA; Snellen E and LogMAR), cataract surgical time, phacoemulsification energy cost, corneal wavefront data, endothelial cell density (ECD), and surgical complications.ResultsSignificant improvements in postoperative visual acuity were observed in both groups (P < 0.05), with Group 2 (FSLA) demonstrating superior outcomes (0.48 ± 0.05/−0.45 ± 0.06; Snellen E/logMAR) compared to Group 1 (0.26 ± 0.07/−0.66 ± 0.15; Snellen E/logMAR). FSLA significantly reduced surgical duration (429.46 s vs. 740.00 s) and cumulative dissipated energy (CDE; 18.90 ± 1.59 vs. 25.24 ± 1.42) without significantly altering higher-order aberrations (0.24 to 0.22 μm). Although ECD decreased postoperatively in both groups, FSLA phacovitrectomy resulted in significantly less endothelial cell loss (227.77 ± 46.85 cells/mm2) compared to conventional phacovitrectomy (389.15 ± 47.87 cells/mm2). No serious complications were reported in either group.ConclusionFSLA phacovitrectomy presents a safe and more efficient alternative over traditional procedures for Oriental patients with medium density nuclear cataract patients with stage 3 macular pucker. Through enhanced IOL centration, shortened surgical times and decreased ECD loss, FSLA led to superior postoperative visual outcomes compared to traditional phacovitrectomy. This study addresses a critical gap in the literature by providing evidence for the benefits of FSLA in Oriental populations, offering valuable insights into its applicability in patients with distinct anatomical variations.